Exoticism as the Threshold of the Fantastic in «La fiebre azul», of Cristina Fernández Cubas (Castilla. Estudios de Literatura, 2021)
This work proposes to analyze the story "La fiebre azul", by Cristina Fernández Cubas, with the objective of determining the influence of the exoticism of the African country where the plot is developed, where superstitions and old beliefs are part of the daily life, in the appearance of the fantastic event. Likewise, it studies the unfolding of the protagonist's personality, a fact that constitutes an illegality in the story, in order to understand its causes and to unravel the metaphor it implies.
Keywords: exoticism; threshold; fantastic; unfolding; Fernández Cubas